Oral and anal sex practices among high school youth in Addis Ababa, Ethiopia - Cherie Amsale; Berhane Yemane (BMC, 2012)
Abstract Background Understanding the full range of sexual behaviors of young people is crucial in developing appropriate interventions to prevent and control sexually transmitted infections including HIV. However, such information is meager in developing countries. The objective of this study was to describe oral and anal sex practices and identify associated factors among high school youth. Methods A cross-sectional study was conducted among high school youth in Addis Ababa, Ethiopia. A multi-stage sampling procedure was followed to select a representative sample of school youth. The total sample size for this study was 3840. Data were collected using a self-administered questionnaire. Data analysis was guided by the ecological framework. Results The overall proportion of people who reported ever having oral sex was 5.4% (190) and that of anal sex was 4.3% (154). Of these 51.6% (98) had oral sex and 57.1% (87) had anal sex in the past 12 months. Multiple partnerships were reported by 61.2% of the respondents who had oral sex and 51.1% of students practicing anal sex. Consistent condom use was reported by 12.2% of those practicing oral sex and 26.1% of anal sex. Reasons for oral and anal sex included prevention of pregnancy, preserving virginity, and reduction of HIV and STIs transmission. Oral sex practice was strongly and significantly associated with perception of best friends engagement in oral sex (AOR = 5.7; 95% CI 3.6-11.2) and having illiterate mothers (AOR = 11.5; 95%CI 6.4-18.5). Similarly, anal sex practice was strongly and significantly associated with favorable attitude towards anal sex (AOR = 6.2; 95%CI 3.8-12.4), and perceived best friends engagement in anal sex (AOR = 9.7; 95%CI 5.4-17.7). Conclusion Considerable proportion of adolescents had engaged in oral and anal sex practices. Multiple sexual partnerships were common while consistent condom use was low. Sexual health education and behavior change communication strategies need to cover a full range of sexual practices.